Evaluation of Virgin Coconut Oil (VCO) Soap Formulation on The Growth Inhibitory Test of Staphylococcus Aureus - Cahyanti, Naomi Dwi; Tumangkeng, Decky Dekres (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2024)
Soap is a product of the saponification reaction consisting of bases and fatty acids, which functions to clean, remove dirt and reduce bacteria on the skin. Virgin coconut oil (VCO) is pure coconut oil which contains lauric acid with antibacterial activity, another function of VCO is also useful in moisturizing the skin. Staphylococcus aureus bacteria are normal flora on the surface of the skin, which can also cause health problems if their numbers and presence are not controlled. The aim of this research was to evaluate soap formulation containing VCO which has antibacterial activity. The research was carried out experimentally with descriptive-quantitative data analysis. The results of this experiment after soap has been storage during 7 days was a solid form of soap, green in color with an apple aroma. The water content value after 7 days of storage according to SNI requirements, that is ≤ 15%. The pH value of soap during storage showed a significant difference based on the Wilcoxon Test with a sig value of 0.042 (<0.05). The antibacterial activity of VCO soap has been confirmed by comparing the inhibition zone of the sample and the positive control of commercial antibacterial soap which was formed after incubation at 370C for 24 hours. The activity of the inhibition zone of Staphylococcus aureus bacteria from samples during 7 days of storage had a significant difference based on the Wilcoxon Test with a sig value of 0.028 (<0.05). Based on research, it has been found that the soap formula contains VCO with antibacterial activity against Staphylococcus aureus.